Hydroponics and Aeroponics in Modern Horticulture: A Review of System Designs and Benefits - Rakshita Chaudhary; Meenakshi Tyagi (International Journal of Trends in Horticulture, 2025)
The quest for efficient and sustainable farming methods around the world has prompted the growing use of soilless cultivation methods like hydroponics and aeroponics. As traditional farming methods face challenges like soil degradation, water scarcity, and climate change, these advanced systems provide viable alternatives that maximize productivity while minimizing resource usage. Hydroponics and aeroponics enable precise control over nutrient delivery, water consumption, and environmental conditions, making them highly efficient solutions for modern horticulture. These techniques are particularly advantageous in urban and controlled-environment agriculture, where space constraints and sustainability concerns necessitate innovative farming approaches. In hydroponic systems, plants are cultivated in nutrient-rich water solutions, either with or without an inert growth medium. Aeroponics, on the other hand, uses plant roots suspended in the air and frequent nutritional solution spraying. Both techniques promote environmentally friendly food production by doing away with the requirement for soil and drastically reducing water waste. Moreover, their ability to support year-round cultivation and higher crop yields makes them attractive for commercial farming ventures. This review explores the fundamental principles, system designs, and major benefits of hydroponics and aeroponics, shedding light on their role in sustainable agriculture. The essay also addresses current issues such high upfront expenditures, the need for technological know-how, and reliance on artificial lighting and energy sources. Future perspectives, including advancements in automation, artificial intelligence, and renewable energy integration, are also examined to assess the potential of hydroponic and aeroponic farming in meeting global food security demands. This review seeks to offer thorough insights into the development and importance of these soilless farming technologies in contemporary horticulture by addressing these factors.
Keywords: Efficient agricultural; Nutrient Film Technique; alternative farming; encountering multiple